Analysis and Strategies for Securing Sanitary and Epidemiological Welfare of the Population of Siberia - M. F. Savchenkov (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
Priorities and directions of development of the Russian economy are connected with the eastern territories. The purpose of the study is to the identify key problems and substantiate indicators of the hygienic and epidemiological welfare of the population of Siberia. Two blocks of characteristics (“public health” and “environment”) are considered in dynamics for 5 years in the context of the subjects of the Siberian Federal District. Four groups of territories differed in terms of the incidence rate and the average life expectancy (ALE) using cluster analysis. It is shown that ALE depends on economic indicators. The incidence is associated with the amount of gross pollutant emissions in the atmospheric air (r = 0.83–0.96; p < 0.001). The assessment of the influence of the habitat on the health of the population at the level of the macroregion allowed to substantiate the hierarchy of the most significant factors. More than 98 % of the environmentally related component of morbidity is associated with the amount of gross emissions of harmful substances in the air (the contribution was 69 %), the provision of the population with doctors (12.6 %) and inpatient beds (6.7 %), the gross regional product (6.5 %), clean water consumption (3 %) and average per capita income (0.8 %). In conclusion, for the successful implementation of preventive strategies, an important stage is the development of a set of solutions for the effective use of resources available in the region (financial, personnel, medical, rehabilitation).